Association Between Concerns About COVID-19 Infection and Blood Donation Intention: Cross-Sectional Survey Study Through a Mobile Communication Platform - Qiuyue Hu; Wei Hu; Lingling Pan; Wenjuan Han; Yue Zheng (JMIR Publications, 2023)
BackgroundThe ongoing COVID-19 pandemic has had an unprecedented impact on blood transfusion and collection. At the beginning of the pandemic, most blood transfusion services had a tough challenge in maintaining an optimal blood inventory. ObjectiveThis study aims to understand the public's psychological cognition and intention toward blood donation as well as the factors influencing their worries. We aimed to find a solution for increasing blood donations and provide a scientific reference for policy formulation regarding blood donation during the COVID-19 pandemic and in the future. MethodsA random survey with a 14-item scale on worries related to blood donation was conducted from December 31, 2022, to January 3, 2023, among residents aged 18-60 years in Zhejiang province via SMS text messaging. The results of 8 worry items in this study were compared with the survey results of March 2022, during which COVID-19 was not considered as an epidemic in Zhejiang province. Chi-square test and logistic regression analysis were performed to analyze the factors affecting respondents' blood donation intention and concerns. The degree of worry about blood donation was assigned from 1 (completely disagree) to 5 (completely agree), and 2-sided t tests were performed to analyze the differences in blood donation intention and worries about blood donation. ResultsIn total, 1254 valid questionnaire responses were obtained. Males accounted for 62.36% (782/1254) of the sample, 78.39% (983/1254) were 18-45 years old, 60.61% (760/1254) had a university education, and 69.06% (866/1254) had no previous blood donation experience. Approximately 36.52% (458/1254) of the public clearly expressed that they had blood donation worries regarding COVID-19. The main concerns of the respondents were temporary physical weakness caused by blood donation, their own physical conditions not meeting the requirements of blood donation, inconvenient location and working hours for blood donation, and family (or friends) worrying about blood donation. Compared with the results in 2022, the results in 2023 regarding the harmful effects of blood donation on health, temporary physical weakness, infection in donated blood, and family (friends) worrying increased significantly (P<.001). The factors influencing blood donation worries regarding COVID-19 were COVID-19 infection status, adverse reactions to the donated blood, family (or friends) worrying, and unsatisfactory blood donation experience. The factors influencing blood donation intention were gender, age, previous blood donation times, blood donation worries regarding COVID-19, harmful effects of blood donation on health, and blood donation anxiety. ConclusionsBlood transfusion services should make full use of the recovery phase of COVID-19 infection as an important time point, publicize the blood donation process and operation standardization, reduce the public's concerns about blood donation, correct negative evaluations, and increase perceived behavioral control and subjective norms.